Referring Patients to Expert Centers After Pancreatectomy Is Too Late to Improve Outcome. Inter-hospital Transfer Analysis in Nationwide Study of 19, 938 Patients. Issue 5 (November 2020) - El Amrani, Mehdi; Lenne, Xavier; Clément, Guillaume; Turrini, Olivier; Theis, Didier; Pruvot, François-René; Bruandet, Amelie; Truant, Stéphanie
Abstract : Objectives: We aimed to analyze the outcomes of interhospital transfer (IHT) patients after pancreatectomy, describe the characteristics of transferring hospitals, and determine the risk factors of transfer and mortality in IHT patients. Background: Implementation of the centralization process is complex and currently unrealized in France. Alternatively, centralization of patients with postoperative complications to high volume centers could reduce postoperative mortality (POM) and failure to rescue (FTR). Methods: All patients undergoing pancreatectomy for cancer between 2012 and 2018 were included. Hospitals' and patients' characteristics were analyzed to determine predictive factors for transfer and FTR. POM was defined as death occurring during the hospital stay and FTR as POM rate among patients with major complications. Results: Overall, 19, 938 patients who underwent pancreatectomy were included, 1164 (5.8%) of whom were transferred. IHT patients were mostly originated from low volume hospitals (60.3% vs 39.7%), from facilities without intensive care unit (46.9% vs 22.4%) or interventional radiology (22.8% vs 12.8%). Among IHT patients, 51% underwent reoperation before transfer and 34.9% experienced hemorrhage complications. The POM was 5.2% and varied significantly between transfer and nontransfer patients (13.3% vs 4.7%, P < 0.001). Patients who experienced major complications after pancreatectomy in low volume hospitals had greater odds of being transferred (Odds Ratio (OR) = 2.46, confidence intervals (CI)95% [1.734; 3.516], P < 0.001). Also, transfer (OR = 2.17, CI95% [1.814; 2.709], P < 0.001) and especially transfer after pancreatectomy in low volume centers (OR = 3.76, CI95% [2.83; 5.01], P < 0.001) were associated with increased FTR rates. Conclusions: Transfers after pancreatectomy were associated with high rates of FTR, especially for patients undergoing surgery in low volume hospitals. Local expertise, resources, and volume of hospitals are mandatory to provide appropriate care after pancreatectomy. Abstract : Supplemental Digital Content is available in the text